Interpersonal Values and Academic Performance Related to Delinquent Behaviors - Molero Jurado, María Del Mar; Pérez Fuentes, María Del Carmen; Luque De La Rosa, Antonio; Martos Martínez, África; Barragán Martín, Ana Belén; Simón Márquez, María del Mar (Frontiers in Psychology, 2016)
The present study analyzes the relation between delinquent behaviors, interpersonal values and academic performance. It also analyzes the possible protective function of interpersonal values against delinquent behaviors. The Interpersonal Values Questionnaire (IVQ) was used to assess interpersonal values, and the Antisocial-Delinquent Behaviors Questionnaire (A-D) was employed to assess antisocial behaviors. The sample was made up of 885 students of Compulsory Secondary Education, aged from 14 to 17 years. The results show that individuals who fail a subject as well as those who repeat a course present higher means in delinquent behaviors. Repeaters present higher means in the values of recognition and leadership, and non-repeaters in the value stimulation, whereas students who do not fail obtain higher scores in the value benevolence. Students with high levels of recognition, independence, and leadership, as well as students with low levels of conformity and benevolence display significantly higher levels of delinquent behaviors. Lastly, the probability of presenting a high level of delinquent behaviors is greater in individuals with: high independence, high leadership, high recognition, low benevolence, and low conformity.